Characterization of Goat Husbandry Practices in Dollo Zone, Somali Regional State Ethiopia (American Journal of Aquaculture and Animal Science, 2023)
The aim of this study was to characterize goat husbandry practices in Dollo zone, Somali Regional state, Ethiopia. Three districts namely Warder, Danod and Daratole were purposively selected based on the goat production potential. Three kebeles were also purposively selected from each district based on the goat production potential. The relevant data for this study were collected through semi-structured questionnaire applied on 156 sample households, key informants interviews, focus group discussions and personal observations the study revealed that the major available water sources in wet season were dams/ponds (92.9%) and pipe water (7.1%), whereas, rig water (65.4%), water wells (17.8%) and dams/ponds (16.7%) were major water sources in dry season and watering frequency of goats varied according to the season, with the dry season having a higher watering frequency due to the inaccessibility of watering points within short distances. The major feed sources for goats during wet season were natural pasture and fodder trees with 63.5% & 36.5%, respectively. On the other side, the major sources of feed in the dry season were natural pasture (42.3%) followed by fodder trees (30.8%) and crop residues (26.9%), respectively. Goats were housed in an open kraal enclosed with branches of acacia tree which don’t protect them from extreme weather conditions. The majority (75.6%) of the goat owners practiced an uncontrolled breeding system. Ethno-veterinary practices through use of herbal and non-herbal ways were practiced in the study area. Drought, feed shortage, water shortage, diseases, predators, and market problems were the major constraints that hindered goat production in the study area. Therefore, the study suggests the need for improving the overall management practices of goats to enhance productivity through awareness creation and extension service. The study also suggests further studies on the implications of suboptimal husbandry practices on goat production and productivity.